2009
DOI: 10.1021/nn8009008
|View full text |Cite
|
Sign up to set email alerts
|

Using Spectroscopic Ellipsometry to Characterize and Apply the Optical Constants of Hollow Gold Nanoparticles

Abstract: In this paper, we report the optical constants (refractive index, extinction coefficient) of self-assembled hollow gold nanoparticle (HGN) monolayers determined through spectroscopic ellipsometry (SE). We prepared a series of HGNs exhibiting various morphologies and surface plasmon resonance (SPR) properties. The extinction coefficient (k) curves of the HGN monolayers exhibited strong SPR peaks located at wavelengths that followed similar trends to those of the SPR positions of the HGNs in solution. The refrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 36 publications
(76 reference statements)
2
51
0
Order By: Relevance
“…We applied spectroscopic ellipsometry to determine the complex refractive index of GeSe film, which is a nondestructive optical technique that allows very precise in situ analysis of the optical properties of thin films through analyzing changes in the polarization state of reflected light from the films with respect to that of incident light. [20][21][22] Figure 1a presents the measured n and k for GeSe films. The real part of the refractive index assumes a very high value of ≈4 in the wavelength range from 500 to 1500 nm, similar to that of silicon, [23] thus implying that GeSe solar cells would perform more favorably with further optical optimization with antireflective coatings or surface structuring.…”
mentioning
confidence: 99%
“…We applied spectroscopic ellipsometry to determine the complex refractive index of GeSe film, which is a nondestructive optical technique that allows very precise in situ analysis of the optical properties of thin films through analyzing changes in the polarization state of reflected light from the films with respect to that of incident light. [20][21][22] Figure 1a presents the measured n and k for GeSe films. The real part of the refractive index assumes a very high value of ≈4 in the wavelength range from 500 to 1500 nm, similar to that of silicon, [23] thus implying that GeSe solar cells would perform more favorably with further optical optimization with antireflective coatings or surface structuring.…”
mentioning
confidence: 99%
“…Previously Wu et al used TEM to demonstrate the formation of pinholes on the surface of Ag nanocubes involved in a galvanic replacement reaction with HAuCl 4 and two of these images can be seen in Fig. 2 [84]. However, Gori's work was the first experimental evidence that pinholes are initiated on only one facet of the crystal lattice and that the reduced metal in a galvanic replacement reaction is deposited first around these pinholes [102].…”
Section: Galvanic Replacementmentioning
confidence: 99%
“…These particles also possess large surface to volume (S/V) ratios, tunable plasmon resonance, pinholes that act as hot spots to further intensify EM surface energy and, as hollow structures, are known to be more sensitive to the refractive index of their surroundings than their solid counterparts [15,66,[81][82][83][84]. Additionally, their scattering and absorption cross-sections can be adjusted through synthesis to maximize efficiency for specific applications, and since the first hyperpolarizabilities (ˇ) of hollow nanoparticles are much larger than those of solid NPs having the same size, HGNs are excellent candidates for any application involving non-linear optics [85,86].…”
Section: Metal Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that different polarization states of the light scattered and reflected by a sample can provide, with appropriate modeling, information about its optical properties, roughness and thickness [8][9][10]. In the context of scattering of light by a sphere placed on a surface, ellipsometric measurements are the most common and practical means of characterization.…”
Section: Introductionmentioning
confidence: 99%